Characterization of mercury resistant and growth promoting Enterobacter sp. from rhizosphere to use as a biofertilizer - Nageena Mobeen; Zakia Latif (Advancements in Life Sciences, 2016)
Background: Mercury occurs naturally in environment, it is heavy metal that exists in three chemical forms like elemental mercury, inorganic mercury and organic mercury. All forms of mercury are problematic for living organism. Currently, the contamination of agricultural land and water systems with mercury has become one of the major environmental issues. The cheapest mode to remove mercury metal and its other forms from the ecosystem is the use of microorganisms. Methods: In this study, initially bacterial species were isolated and purified from nodule like structures on roots and stems of plants on MacConkey agar medium. Further screening for resistance to mercury was done on N- agar medium supplemented with different concentration of HgCl2 (20, 30, 40 and 50 µg/mL). Well plate method was used for the determination of bacterial strains having maximum ability to detoxify mercury. Selected bacterial strains were subjected to different biochemical tests for characterization and other metabolic tests were also performed to characterize their capabilities. Results: All strains were highly resistant to HgCl2 at the concentration of 20 µg/mL and moderately resistant at 30 µg/mL. Bacterial strain S-2 was moderately resistant and S-3 was least resistant at 40 µg/ml whereas S-2 was least resistant at 50 µg/ml. Selected bacterial strains were positive for nitrogen fixation and protease production, negative for phosphate solubilization but only S-1 was positive for hydrogen cyanide (HCN). Bacterial species were molecular characterized by 16S rDNA sequencing as Enterobacter cloacae (KJ857483, KJ857484 and KJ857485: NCBI GeneBank). Conclusion: Selected Enterobacter sp. exhibiting multiple characteristics can be used as biofertilizer in mercury polluted land for sustainable agriculture.